Childhood Adversity and Dimensional Variations in Adult Sustained Attention - Vogel, Sarah C.; Esterman, Michael; DeGutis, Joseph; Wilmer, Jeremy B.; Ressler, Kerry J.; Germine, Laura T. (Frontiers in Psychology, 2020)
Background & Objective Sustained attention is a transdiagnostic phenotype linked with most forms of psychopathology. We sought to understand factors that influence the development of sustained attention, by looking at the relationship between childhood adversity and adult sustained attention. Participants, Setting, and Methods Participants were 5,973 TestMyBrain.org visitors from English-speaking countries who completed a continuous performance task (gradCPT) of sustained attention and a childhood adversity questionnaire. We analyzed gradCPT performance using a signal detection approach. Results Discrimination ability (the main metric of performance on the gradCPT) was associated with total childhood adversity load, even when controlling for covariates related to age, gender, parental education, race, country of origin, and relative socioeconomic status (=-0.079, b=-0.032, 95% CI [-0.043, -0.021], p<0.001 ). Conclusions Our results demonstrate that attention differences related to childhood adversity exposure can (1) be measured using brief, performance-based measures of sustained attention, (2) persist into adulthood, and (3) be detected at the population level. These results, paired with the well-documented associations between sustained attention and psychopathology, indicate that sustained attention may be an important mechanism for understanding early influences on mental health.